PERLINDUNGAN HUKUM TERHADAP KORBAN INVESTASIILEGAL SKEMA PONZI - Adri Fasya Saputra (2023)
Technology through media networks is very developed, so that in their daily lives people cannot be separated from the internet, including the economy. Technological developments in terms of investment can be made without the need to come to an investment company, but only download an application and register online. In addition to the convenience of registering, the public is also offered a variety of investment products and can invest according to their wishes. This can become a problem if people are not careful in choosing the product they want to invest in and the worst possibility is becoming a victim of illegal or fraudulent investment. Illegal investments can be found in ponzi schemes to attract victims. The formulation of the problems in this study are: (1) What is the form of legal protection for victims of illegal Ponzi scheme investments? (2) What is the role of the government towards victims of illegal investments who have been operating in collecting funds without permission in the community? This research is normative legal research, with a statute approach and a case approach. This research shows that if an investment company has a valid permit to collect public funds, then the company will be given legal protection by the state. The results of the study show that legal protection can be realized by the government if the investment company has obtained a business license to collect public funds. If the investment company has a legal permit, the victim will receive legal protection based on Article 30 paragraph 1 letter b Law Number 21 of 2011 concerning Otoritas Jasa Keuangan and supported by Article 4 letter a Supreme Court Regulation Number 1 of 2022 concerning Tata Cara Penyelesaian Permohonan dan Pemberian Restitusi dan Kompensasi Kepada Korban Tindak Pidana. The role of the government through Otoritas Jasa Keuangan is to handle it with the help of Kominfo to block illegal investment content with ponzi schemes, however, compensation for victims of illegal investments cannot be obtained.